No-wait resource allocation flowshop scheduling with learning effect under limited cost availability. (3rd April 2018) - Tian, Yu; Xu, Ming; Jiang, Chong; Wang, Ji-Bo; Wang, Xiao-Yuan
Abstract: This article considers the no-wait flowshop scheduling with learning effect and resource allocation on two-machine. Our goal is to find the optimal resource allocations and job sequence that minimize the scheduling criterion (the total weighted resource consumption) subject to the constraint that the total weighted resource consumption (the scheduling criterion) is less than or equal to a given constant, where the schedule criteria include weighted makespan, total completion (waiting) time and total absolute differences in completion (waiting) times. We show that these two problems are polynomially solvable respectively.